Study into the synthesis, characterisation and applications of Vanadium-based metal organic frameworks, using 1, 2, 4, 5-benzenetetracarboxylic acid - Feldmann, Wesley (Rhodes University, Faculty of Science, Department of Chemistry, 2016)
This study focussed on the synthesis, characterisation and catalytic application of synthesised vanadium-based Metal-Organic Frameworks using 1,2,4,5-benzenetetracarboxylic acid as a ligand. A number of synthetic methods were tested in multiple attempts to synthesise a V-MOF, these included; ambient, gel, reflux and solvothermal methods of synthesis. Two products of interest were identified, an ambient synthesis produced a vanadium-based complex with the empirical formula: V2O2(Na2H2B4C).6H2O (RU-V2) and a solvothermal synthesis produced a MOF with the empirical formula: V2O2(H2O)2(B4C) (RU-V1). Both products were characterised using elemental analysis, infrared spectroscopy, thermogravimetric analysis, differential scanning calorimetry and X-ray powder diffraction. The catalytic activity of these products was tested, alongside the activity of the solid decavanadate ion, for the conversion of cyclohexene to cyclohexene oxide. The decavanadate ion was included to determine if the ion was catalytically active in the solid state, to potentially be used in the construction of a future MOF or V-complex. The reaction for the conversion of cyclohexene to cyclohexene oxide was chosen, as it has been previously conducted using a V-MOF and was found to be successful. The product of the reaction, the epoxide: cyclohexene oxide, is a very useful precursor for a number of reactions involved in the pharmaceutical industry, so developing catalysts which are able to convert cyclohexene to the epoxide with high yields and selectivities are well sought after in industry. The results of the catalytic reactions were varied, as the materials exhibited high yields and selectivities to the epoxide, but these results were only obtained when water was present in the reaction mixture. Water was able to bring about the cleavage of the bonds between the metal and ligand in a highly coordinated framework, at a faster rate than other solvents, such as decane. This ultimately leads to the structural decomposition of the entire complex or framework, depending upon the reaction time. The use of water was a double edged sword in that it was required to initiate the catalytic reaction, but was also the reason that the catalytic materials were noted to decompose over time. The solid decavanadate ion was only noted to exhibit homogeneous activity by dissolving into the small volume of water present in the reaction mixture. The study proved that using a multidentate ligand such as 1,2,4,5-benzenetetracarboxylic acid yielded products which were highly coordinated in nature and would therefore not have large open spaces associated with them, which is commonly observed with other MOFs. Instead the closed nature of the synthesised complexes and frameworks offered a different environment for catalytic reactions, where the small pores/channels had a controlling and inhibiting effect on the reaction. The conversion of cyclohexene to the epoxide is accompanied with a number of undesired side products, so when using the synthesised closed-natured MOF, it was found that there was a greater selectivity for the epoxide over other potential products. This indicates that close natured MOFs may find application in catalytic reactions which require high selectivities for a particular product.
Keywords: Uncatalogued